2022
DOI: 10.1002/ps.7147
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral modes of action of the novel compound GLY‐15 containing pyrimidine heterocycle and moroxydine skeleton against tobacco mosaic virus

Abstract: BACKGROUND Plant virus diseases are difficult to prevent and control, causing serious economic losses to the agricultural production world. To develop new pesticides with antiviral activity, a serial of compounds containing the structure of pyrimidine and moroxydine were synthesized, among which GLY‐15 exhibited good antiviral activity against tobacco mosaic virus (TMV), while the mechanism of antiviral activity remains to be clarified. RESULTS GLY‐15 treatment significantly inhibited the formation of necrotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…53 In addition, we have previously revealed that the binding affinity of pyrimidine moroxydine derivatives to the viral components (TMV CP and Hel) predicted by molecular docking positively correlated with the inhibitory effects of the compounds on the infection of TMV in plants. 4 In this study, the results of molecular docking indicated that anisomycin can potentially interact with viral proteins of TMV and PVY. The helicase domain of TMV replicase plays critical roles during viral replication, 54 while the coat protein is required for the genome assembly as well as in the systemic infection of the virus.…”
Section: Anisomycin Can Potentially Bind With Viral Proteins Of Tmv A...mentioning
confidence: 67%
See 1 more Smart Citation
“…53 In addition, we have previously revealed that the binding affinity of pyrimidine moroxydine derivatives to the viral components (TMV CP and Hel) predicted by molecular docking positively correlated with the inhibitory effects of the compounds on the infection of TMV in plants. 4 In this study, the results of molecular docking indicated that anisomycin can potentially interact with viral proteins of TMV and PVY. The helicase domain of TMV replicase plays critical roles during viral replication, 54 while the coat protein is required for the genome assembly as well as in the systemic infection of the virus.…”
Section: Anisomycin Can Potentially Bind With Viral Proteins Of Tmv A...mentioning
confidence: 67%
“…TMV and PVY are both enlisted in the top 10 important plant viruses in plant pathology and effective management of these viruses has become a significant issue . Until now, many lines of studies have been performed to screen and develop agents against TMV. However, effective management for the control of potyviruses is still very limited.…”
Section: Introductionmentioning
confidence: 99%
“…The pesticide GLY-15 has a good antiviral activity against tobacco Mosaic virus in plants. It induces a stress response in plants, in which the expression of 12 key genes including glucan-1, 3-βglucosidase is significantly up-regulated [31]. Other studies have shown that glucan endo-1, 3-βglucosidase is involved in plant response to soil alkaline stress [32].…”
Section: Discussionmentioning
confidence: 99%
“…69 Moreover, they found that orange peel essential oil was added to compound 67b as an auxiliary to display more satisfactory activity (Figure 12). Compound 68 70 was confirmed to possess inhibitory properties against systemic infection of TMV through the utilization of visualized viral infection. Furthermore, it demonstrated significant suppression of the RNA accumulation of TMV in individual tobacco cells (Figure 12).…”
Section: ■ Antiviral Activitymentioning
confidence: 97%